KONTRIBUSI PEMIKIRAN METODE TAFSIR IBNU TAIMIYYAH: Telaah atas Buku Muqaddimah Fi Ushuli al-Tafsir - Waliko Waliko (MAGHZA, 2016)
This writing is analytic the book of Muqoddimag Fi Ushuli al-Tafsir issued by Ibnu Taimiyah. In this book give guidance ( Manhaj) in understanding the Qur'an by obtaining the basic interpretation discipline and giving distinct among scholars and made tarjih among the differences. The book consists of five chapters. Chapter one is Prophet Muhammad explained the meaning of Qur’an among friends. Chapter two the differences among salaf ulama in Tafseer is a difference of tanawwu’ fasal. Chapter three kind of differences, naqal side, and istidlal. Chapter four in different interpretation from istidlal side. Chapter five is the best method Tafseer. In making interpretation there are two ways: tafseer by naqli and tafseer by istidlal or ma’qul. In this case, Ibnu Taimiyah commitment to the naqly way and giving critical for those who in the second method.